Clinical and mechanistic effects of cladribine in relapsing multiple sclerosis: 2-year results from the MAGNIFY-MS Study - Klaus Schmierer; Heinz Wiendl; Frederik Barkhof; Xavier Montalban; Anat Achiron; Tobias Derfuss; Andrew Chan; Suzanne Hodgkinson; Alexandre Prat; Letizia Leocani; Finn Sellebjerg; Patrick Vermersch; et al. (Therapeutic Advances in Neurological Disorders)
Background: Cladribine, an oral prodrug, penetrates the blood–brain barrier, impacting biomarkers of disease progression within the central nervous system. Objectives: Describe disease activity in cladribine tablets (CladT)-treated people with highly active relapsing multiple sclerosis (pwRMS) using clinical outcomes and biomarkers. Design: MAGNIFY-MS was an open-label, single-arm, phase IV trial with four sub-studies. Participants were grouped by previous treatment (Tx); Tx-naïve versus Tx-experienced; those with previous exposure to second-line therapies were excluded. This analysis describes cerebrospinal fluid (CSF) and optical coherence tomography (OCT) sub-studies. CSF sub-study participants were stratified by the number of oligoclonal bands (OCBs) at baseline (≥2/≥4). Methods: Logistic regression analysis is reported for no evidence of disease activity (NEDA)-3 and no evidence of progression or active disease (NEPAD) at Year (Y)1 and Y2, and annualized relapse rate (ARR) at Y2. Changes in intrathecal (OCBs, kappa free light chain [KFLC], immunoglobulin [Ig]G and IgM indices), OCT measures, and neuroaxonal degeneration (neurofilament light chain [NfL]) biomarkers are reported at baseline, month (M)12, and M24. Results: MAGNIFY-MS included 270 pwRMS; 28 and 36 were included in the CSF and OCT sub-studies, respectively. In Y2, estimated rates of NEDA-3 were 64.1% overall and 69.1% in the Tx-naïve group. The estimated rate of NEPAD overall was 60.2% in Y2. The estimated ARR was 0.09 from baseline to M24 (Tx-naïve participants, 0.04). In participants with ≥2 OCBs at baseline ( n  = 17), 76.5% had OCB reduction or disappearance at least once in the study. KFLC and IgG indices were reduced at M24 versus baseline. Sustained reductions were observed in median NfL, while IgG and IgM remained within normal ranges for most participants. Mean OCT measurements showed no retinal nerve fiber thinning. Conclusion: For CladT-treated pwRMS, disease activity and biomarkers of intrathecal inflammation and neuroaxonal damage were reduced versus baseline. Trial registration: ClinicalTrials.gov identifier, NCT03364036. Date registered: June 12, 2017. Date first patient enrolled: May 28, 2018. https://clinicaltrials.gov/study/NCT03364036 . Extension study ClinicalTrials.gov Identifier: NCT04783935. Date registered: March 05, 2021. Date first patient enrolled: March 10, 2021. https://clinicaltrials.gov/study/NCT04783935 .